PENERAPAN MODEL PEMBELAJARAN KOOPERATIFTIPESTUDENT TEAMS ACHIEVEMENT DIVISION (STAD)UNTUK MENINGKATKAN HASIL BELAJARIPASISWA KELAS VII2 SMP N 6 TANAH PUTIHTAHUN PELAJARAN 2015/2016 - Fauziah, Yuslim; ', Juneti; ', Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This research is class room action research which is aimed to IPA studying achievement by implementing cooperative learning of Student Teams Achievement Division(STAD)in class VII2 SMP N 6 Tanah Putih in Academic Year 2015/2016.This research was conducted in Maret-April 2016. The subject of this research was student of class VII2ofSMP N 6 Tanah Putih. The number of students was24 students (15boys and 9 girls). The Parameter was students studying achievement consisted of comprehension ability, students passing individually, studens activitiesand teachers activities.The averageof students comprehension ability in cycle 1 was 75.79% (moderate) increased became 78.54% (moderate). The students passing studying in cycle 1 was 66.67% (pass) increased in cycle 2 became 79.17% (pass). The average of award in cycle 1 was the fifth group is awarded as a super group then it improved in cycle 2 became 2 groups received an award as a super group and 3 groups received an award as great group.Average of studens activities in cycle 1 was 87.62% (verygood) increased in cycle 2 became 94.81% (very good).Average of teachers activities in cycle 1 and 2 was 100% (very good).From the result of this research it can be concluded that the implementation of cooperative learning the Student Teams Achievement Division(STAD) can improve students IPA studying achievements in class VII2 SMP N 6 Tanah Putih in Academic Year 2015/2016.Keywords: IPA studying achiement, cooperative learning of student teams achievement division (STAD)